VIDROHA, VEDANA, NAKAR: THE TRINITY OF RESISTANCE IN BABURAO BAGUL’S WHEN I HID MY CASTE STORIES - Praveen Toppo; Sahabuddin Ahamed (International Journal of Cultural and Social Science, 2026)
This study critically examines the articulation of subaltern consciousness in Baburao Bagul’s short story collection When I Hid My Caste Stories, a foundational text in Dalit literature. Through a close analysis of ten selected stories, the research investigates how Bagul formulates a distinctive Dalit literary aesthetic grounded in the intersecting themes of vidroha (revolt), vedana (pain), and nakar (dissent). These thematic vectors constitute the foundational grammar of Dalit expression, encapsulating both personal and collective experiences of caste-based marginalization existence in modern India. Moving beyond a mere documentation of systemic oppression, Bagul’s narratives delve into the psychological, social, and existential dimensions of Dalit life. They reveal the complex interplay of caste discrimination, economic marginalization, gender subjugation, and cultural erasure, while simultaneously foregrounding Dalit resistance, agency, and evolving identity. Bagul’s literary strategies transform individual trauma into a universal humanistic discourse centred on dignity and survival. The analysis is informed by a theoretical framework that combines subaltern studies, intersectionality, and Dalit literary criticism. This study argues that Bagul’s work not only occupies a foundational place in Indian literature, but also offers a powerful model for the aesthetics of subaltern representation and protest within modern Indian literary discourse.